The Impact of Effectiveness of PAI Decentralization Curriculum to Improve the Quality of Teachers and Students - Rustin, Ddilla; Madjid, Abd. (Universitas Muhammadiyah Mataram, 2026)
Islamic Religious Education (PAI) plays a vital role in shaping students’ character, morals, and concern for socio-cultural diversity and environmental sustainability. To address contemporary challenges and contextual needs, a decentralization policy in the PAI curriculum is applied. This policy grants regional authorities the flexibility to adapt teaching materials in line with local cultural values and community needs. The main goal is to enhance the relevance, effectiveness, and appeal of PAI education by making it more contextual and responsive to local conditions. Education is not only a medium for knowledge and character development but also a platform to cultivate students’ awareness and responsibility toward preserving their environment and community. Curriculum innovation that integrates religious values, local wisdom, and environmental insight becomes a strategic approach to shaping a generation that is faithful, caring, and ecologically literate. This study uses a systematic literature review method, analysing 20 articles from Google Scholar published between 2020 and 2024, with the keyword’s “decentralization” and “PAI curriculum.” The findings indicate that curriculum decentralization can improve the contextuality and relevance of Islamic education but also encounters challenges such as disparities in regional capacities and limited coordination among policy stakeholders.